2016
DOI: 10.5812/hepatmon.37806
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping and Mutation Pattern in the Overlapping MHR Region of HBV Isolates in Southern Khorasan, Eastern Iran

Abstract: BackgroundHepatitis B virus, with 8 known distinct genotypes, is one of the most serious health problems which results to liver injuries. The surface gene of Hepatitis B virus completely overlaps with the polymerase gene. Mutations in the RT gene result in changes in the overlapping hepatitis B surface antigen.ObjectivesThe present study aimed to evaluate the genotypes and prevalence of mutations in a segment of S and RT gene in HBV isolates in Southern Khorasan, Iran.MethodsThis was a population-based study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 39 publications
3
31
1
Order By: Relevance
“…The replication cycle of HBV involves a lot of genetic instability, causing approximately 1.4 × 10 −5 to 3.2 × 10 −5 substitutions per nucleotide site. 30 Most prevalent escape mutant that observed in this study was Q129H, and in lower range I92T, T125A, and P105A, which all of them reported in previous studies as escape mutations 31 or association to OBI. 32 High rate of mutation might defect the replication cycle or producing S variants undetectable with serologic assays, and lead to incidence of OBI.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The replication cycle of HBV involves a lot of genetic instability, causing approximately 1.4 × 10 −5 to 3.2 × 10 −5 substitutions per nucleotide site. 30 Most prevalent escape mutant that observed in this study was Q129H, and in lower range I92T, T125A, and P105A, which all of them reported in previous studies as escape mutations 31 or association to OBI. 32 High rate of mutation might defect the replication cycle or producing S variants undetectable with serologic assays, and lead to incidence of OBI.…”
Section: Discussionsupporting
confidence: 50%
“…35 As S gene completely is in overlap with Pol gene, there were mutations in the corresponding region of RT, such as L80I, S85F, R110G, and L91I, which were repeatedly reported in previous studies as resistance associated. 31,36 Positions of RT at 80, 85, 91, and 110 are functional in the first domain of RT and are potentially prone to resistance in the presence of mutations. [37][38][39] Phylogenetic analysis revealed that all isolates of current study belong to genotype D, subgenotype D1, except one that was D4.…”
Section: Discussionmentioning
confidence: 99%
“…However, in low-endemicity areas, hepatitis B is mainly transmitted through unsafe sex and injection drug abuse during adulthood (8). Blood transfusion is also another hepatitis B transmission route (9). The most common transmission routes in Iran are maternal-infant transmission and injection drug abuse.…”
Section: Introductionmentioning
confidence: 99%
“…The most common and most serious types of viral hepatitis are hepatitis B and C. The prevalence of hepatitis B and C in Iran is 1.2% -5% and 0.6%, respectively (1-3). Moreover, the prevalence of hepatitis B in Birjand, Iran, is 1.6%, on average (3,4).…”
Section: Introductionmentioning
confidence: 99%